The Role of Competence and Financial Planning in Supporting the Readiness of the Next Generation in Family Businesses in Indonesia - Bima Bryantama; Nayla Qur’ana Magrifah Al – Laily; Rahel Cornelia Alvani Mardianto; Uki Yonda Asepta (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
This study aims to analyze the role of competence and financial planning in supporting successor readiness in family businesses in Indonesia. This research applies a qualitative approach using a literature review method by examining journal articles, academic books, previous studies, and relevant official documents. The findings indicate that competence developed through formal education, informal training, mentoring, internships, and direct operational involvement plays an important role in shaping successors’ analytical ability, leadership capacity, and legitimacy. In addition, structured financial planning helps separate family and business assets, improve financial transparency, and reduce potential internal conflicts. This study concludes that the integration of competence and financial planning is an important factor in strengthening succession success and ensuring the sustainability of family businesses in Indonesia.